Analysis Comparison of the Efficiency of Using MYOB and ACCURATE in Learning Accounting for Vocational High School Students : ANALISIS PERBANDINGAN EFISIENSI PENGGUNAAN MYOB DAN ACCURATE DALAM PEMBELAJARAN AKUNTANSI UNTUK SISWA SEKOLAH MENENGAH KEJURUAN - Febriana, Windy (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract.This study aims to compare the efficiency of MYOB and Accurate accounting software in vocational high school (SMK) accounting education using a quantitative approach. Data was collected through tests, questionnaires, and observations to measure students’ conceptual understanding, task completion speed, accuracy, and satisfaction levels. The results indicate that MYOB is easier to understand and enhances learning motivation, enabling students to complete basic tasks more efficiently. In contrast, Accurate offers more comprehensive features aligned with accounting standards, making it more suitable for handling complex transactions. While student satisfaction levels with both software were relatively similar, individual preferences varied based on learning styles and comprehension levels. The findings highlight MYOB’s superiority in usability and foundational efficiency, whereas Accurate proves more effective for advanced accounting instruction. This research provides valuable insights for vocational accounting education, serving as a reference for teachers and curriculum developers in selecting appropriate accounting software tailored to learning objectives. Abstrak. Penelitian ini bertujuan membandingkan efisiensi penggunaan software akuntansi MYOB dan Accurate dalam pembelajaran akuntansi siswa SMK menggunakan metode kuantitatif. Data dikumpulkan melalui tes, kuesioner, dan observasi untuk mengukur pemahaman konsep, kecepatan, ketepatan tugas, serta kepuasan siswa. Hasil menunjukkan bahwa MYOB lebih mudah dipahami dan meningkatkan motivasi belajar, sehingga siswa lebih cepat menyelesaikan tugas sederhana. Di sisi lain, Accurate memiliki fitur lebih lengkap sesuai standar akuntansi, membuatnya lebih cocok untuk transaksi kompleks. Meskipun tingkat kepuasan siswa terhadap kedua software relatif sama, preferensi individu bergantung pada gaya belajar dan tingkat pemahaman. Implikasi penelitian ini penting bagi pendidikan akuntansi SMK, memberikan referensi bagi guru dan pengembang kurikulum dalam memilih software yang sesuai kebutuhan pembelajaran. Dengan demikian, MYOB lebih unggul dalam aspek kemudahan dan efisiensi dasar, sementara Accurate lebih efektif untuk pembelajaran akuntansi mendalam.